Development of a Flipbook-Based E-Module to Enhance Learning Outcomes in Manufacturing Design for Vocational High School Students - Rahmagandi, Irma Oktariamlati; Khumaedi, Muhammad; Anis, Samsudin (Journal of Vocational and Career Education, 2024)
Limited understanding of 2D and 3D sketching using Autodesk Inventor Drawing, constrained by conventional teaching methods and the lack of adequate learning modules, remains a significant challenge in the manufacturing design course for Mechanical Engineering students at SMK Negeri 5 Semarang. This issue directly impacts student learning outcomes. This study aims to develop a flipbook-based e-module to improve learning achievements, with its effectiveness analyzed through t-tests and N-gain tests. The research employed the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). An experimental method was applied using a pretest-posttest control group design, involving 64 students divided into an experimental class and a control class. The results indicated that the developed e-module, including its content, media, and assessment instruments, was deemed feasible for use. Statistical analysis revealed a significant improvement in the experimental class compared to the control class, as evidenced by a t-value greater than the critical t-table value (7.664 > 1.998). Furthermore, the N-gain test showed a moderate increase in the experimental class (0.56) compared to the control class (0.32), demonstrating an enhancement in student learning outcomes. This study highlights the positive impact of integrating technology into education and emphasizes the importance of innovative teaching methods in advancing student competencies in manufacturing design.